KARATERISTIK KOPERASIUNTUK MEMBEDAKAN PENGARUHNYA TERHADAP PERMINTAAN JASA AUDIT EKTERNAL - Oyong Lisa (RELASI : JURNAL EKONOMI, 2015)
The fact that coorperation is one form of business entity which is less utilizing the services of an external audit, while the performance coorporation.snow in quantitative scale continues to increase. This research was conducted for 120 coorporation  in East Java. The data collected in this study were analyzed using Discriminant Analysis.The aim was to observe the effect obvervation Company members, the size of the Corporation, the amount of liabilities, capital structure and rate of profitto external audit. Based Characteristic analysis shows that the cooperative can distinguish between the effect of the cooperative that uses external audit services to cooperatives that do not use a partial audit services eksternal. There is are variable that is not significant, namely capital structure. This means that the capital structure variables as the independent variables used in this study partially not significantly affect the conduct cooperative demand for external audit and audit services did not do audit external.Variabel most distinguish two groups of audit external is a variable rate of profit and the smallest influence the amount of liability, while the capital structure is not a variable that distinguishes the two groups of audit external.